An outbreak of equine sarcoid in a population of Cape mountain zebra (Equus zebra zebra) - a retrospective study - Bertschinger, H.J. (Hendrik Jan) (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2007.